Preemergence and Early Postemergence Weed Control with Instigate, Glyphosate, Realm Q, Atrazine, Dicamba, Corvus, Acuron, and Resicore in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Palmer amaranth, kochia, quinoa, common sunflower, and green foxtail control was excellent with most treatments. Crabgrass control was also good with most treatments. Crabgrass control with Realm Q (rimsulfuron + mesotrione) + atrazine, dicamba, and glyphosate; and with Corvus (isoxaflutole + thiencarbazone) + atrazine, dicamba, and glyphosate was slightly less by 73 DAPT. The exceptional weed control with these herbicides resulted in grain yields that were 108 to 125 bu/a greater than in the untreated plots. However, there were no differences among herbicide treatments for corn yield.
Keywords: residual control